Adaptive control for athletic motor skills excellence - Zagrevskiy, V.I.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop adaptive control software to model movement of an object from the initial phase when the execution deviates from the execution standard to the required standard state with the relevant kinematics.